1986
DOI: 10.1016/s0022-5347(17)45085-3
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Treatment of Metastatic Renal Cancer

Abstract: Radical nephrectomy and excision of metastases were performed in 21 patients with metastatic renal cell carcinoma. Followup was 12 years. Eight patients had metastases at the time of diagnosis and survived an average of 54 months, with 50 per cent alive 5 years postoperatively. Metastases developed after nephrectomy for localized disease in 13 patients. After extirpation of the secondary lesions these 13 patients survived an average of 38 months and 25 per cent were alive at 5 years. Survival varied with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
5

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 8 publications
3
13
0
5
Order By: Relevance
“…Minervini et al (2001) did not observe different 5-year-survival rates in 167 patients undergoing either radical tumor nephrectomy alone or in combination with extensive lymph node dissection. These findings are in line with previous reports by Bassil et al (1985) and Golimbu et al (1986). In contrast, observations by Schafhauser et al (1999) in more than 1000 patients with renal cancer suggest a survival benefit for patients after extensive lymph node dissection.…”
Section: Lymph Node Metastasessupporting
confidence: 93%
“…Minervini et al (2001) did not observe different 5-year-survival rates in 167 patients undergoing either radical tumor nephrectomy alone or in combination with extensive lymph node dissection. These findings are in line with previous reports by Bassil et al (1985) and Golimbu et al (1986). In contrast, observations by Schafhauser et al (1999) in more than 1000 patients with renal cancer suggest a survival benefit for patients after extensive lymph node dissection.…”
Section: Lymph Node Metastasessupporting
confidence: 93%
“…Besides the 'classical' prognostic factors identified by From 1977 to 1995, 79 patients (54 men and 25 women) underwent surgery in the Urology Department, Golimbu et al [2], others reported that the diagnosis of a Hannover Medical School, for RCC with propagation of a tumour thrombus into the IVC. Sixty-three patients Accepted for publication 11 March 1997 presented with a VCT bordering the infrahepatic section (36%) were diagnosed as having distant metastases during routine pre-operative tumour staging, five of of the IVC caudal to the hepatic veins and 16 superior to the hepatic veins, above the diaphragm or in the whom showed more than one area of tumour (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…These surprisingly the long-term survival of patients with RCC but no VCT. The prognostic importance of propagation of tumour positive results can be compared with the 5-year survival rate reported in the study by Golimbu et al [2], in which thrombus into the IVC and cranial extension was investigated and correlated with other tumour characteristics, 326 patients with RCC were investigated, where the longterm survival rate was 88% for those presenting with both by univariate and multivariate analyses, to assess the value of intracaval extension as a possible indepenearly stages of hypernephroma. The survival rates for those with additional tumour characteristics were 67% dent prognostic factor for patients with RCC.…”
mentioning
confidence: 99%
“…Renal cell carcinomas (RCC) generally have a poor prognosis since, once the diagnosis is made, metastases are already present in 30% of the cases while 50% of the patients develop them at a later date [5,13]. At present there is no efficient systemic treatment for metastatic RCC, since neither radiation nor chemotherapy has been very effective [4,6,12].…”
Section: Introductionmentioning
confidence: 99%